Controllable volatile to nonvolatile resistive switching conversion and conductive filaments engineering in Cu/ZrO2/Pt devices. (13th October 2016) - Du, Gang; Li, Hongxia; Mao, Qinan; Ji, Zhenguo
Abstract: Coexistence of volatile and nonvolatile resistive switching characteristics in a single Cu/ZrO2 /Pt device was demonstrated by controlling the current compliance ( I CC ). The grain boundaries as well as the increased amount of oxygen vacancies in the polycrystalline ZrO2 films offer the opportunity to reduce the switching kinetics and to engineer the dimension and density of the conductive filaments (CFs). Only one CF with an atomic scale diameter was formed when the I CC was lower, whereas this tiny CF was unstable and would be annihilated spontaneously when the applied voltage reduced to zero, exhibiting a typical volatile property. The size of the CF grew with the further increasing of the I CC . Quantized conductance was observed during the switching process, corresponding to the atomic-size variation of the CF. However, robust multiple CFs were formed and dominate the totally nonvolatile switching behaviors when a large enough I CC was adopted. This work demonstrates the feasibility of modulating the switching kinetics to realize the volatile and nonvolatile characteristics for high-density storage and neuromorphic applications.